1985
DOI: 10.1136/ard.44.9.575
|View full text |Cite
|
Sign up to set email alerts
|

Bone turnover in early rheumatoid arthritis. 1. Biochemical and kinetic indexes.

Abstract: and the 2National Institute for Biological Standards and Control, London SUMMARY Biochemical, hormonal, and kinetic indexes of bone turnover were measured in 17 ambulant female patients with rheumatoid arthritis (RA) of recent onset (mean disease duration 14-2 months) and 19 controls. Mean serum osteocalcin concentration and 85Sr accretion rates were reduced and mean urinary hydroxyproline-creatinine ratios were increased in RA, but these differences were not significant compared with control values. Mean tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
3

Year Published

1987
1987
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 31 publications
1
11
0
3
Order By: Relevance
“…In the present study, we found no statistically significant difference between the urinary Ca:Cr ratio in patients and controls, but urinary 0HP:Cr ratios were increased in both groups of patients. This is consistent with the findings of Verstraeten and Dequeker (20) and with our own previous findings in postmenopausal women with recent-onset RA (22), in whom 0HP:Cr ratios showed a tendency to be higher.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we found no statistically significant difference between the urinary Ca:Cr ratio in patients and controls, but urinary 0HP:Cr ratios were increased in both groups of patients. This is consistent with the findings of Verstraeten and Dequeker (20) and with our own previous findings in postmenopausal women with recent-onset RA (22), in whom 0HP:Cr ratios showed a tendency to be higher.…”
Section: Discussionsupporting
confidence: 93%
“…The total amount of 25 hydroxyvitamin D is reported to be normal in all (12,14,17,18) but one study (13); the serum concentrations of 1,25 dihydroxyvitamin D are reported to be normal (12,13,18) or slightly increased (17). An increase was found in patients with a short disease duration, who also had an increased fractional calcium absorption (21).…”
Section: Generalised Bone Involvementmentioning
confidence: 89%
“…In RA the hydroxyproline excretion also re-flects disease activity, since the turnover of the complement protein Clq is also measured by the hydroxyproline excretion (20). Urinary calcium excretion is reported to be normal (12,17) or slightly decreased (13,15 ). Urinary hydroxyproline excretion is reported to be increased (12,13) or decreased 05).…”
Section: Generalised Bone Involvementmentioning
confidence: 93%
“…Raised parathyroid hormone levels have also been reported in rheumatoid arthritis,35 though this finding has not been universal,36 especially when mid-region assays have been used. 29 The most detailed bone histomorphometric study in rheumatoid arthritis to date is that of Duncan et al,2 who examined indices of bone formation in rib biopsy specimens using tetracycline labelling. Although he interpreted his results as supporting increased resorption rather than decreased formation as the cause of bone loss, reduced tetracycline uptake and osteoid surface in three out of five and four out of seven patients respectively indicates a reduction in bone formation.…”
Section: Discussionmentioning
confidence: 99%